Understanding the Morality of Teaching Profession With Reference To Immanuel Kant's Conceptualization of Good Will versus Duty - Amukowa, Wycliffe; Nderitu, Moses K. (Journal of Education and Human Development, 2013)
This paper seeks an articulation of the morality of actions and attitudes relating to the teaching profession. Its essence is a contribution to the understanding of motivations and principles guiding the choice of teaching as a profession and the consequent engagement of its duty.
Keywords: Teaching; Teachers; Profession; Good Will; Duty